2019
DOI: 10.1029/2019gl083712
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Local Time‐Resolved Examination of Radiation Belt Dynamics during High‐Speed Solar Wind Speed‐Triggered Substorm Clusters

Abstract: Particle observations from low Earth orbiting satellites are used to undertake superposed epoch analysis around clusters of substorms, in order to investigate radiation belt dynamical responses to mild geomagnetic disturbances. Medium energy electrons and protons have drift periods long enough to discriminate between processes occurring at different magnetic local time, such as magnetopause shadowing, plasma wave activity, and substorm injections. Analysis shows that magnetopause shadowing produces clear loss … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 11 publications
(31 citation statements)
references
References 42 publications
1
30
0
Order By: Relevance
“…This work initially identified HILDCAA activity present in the magnetosphere linked to large amplitude Alfvén waves in the solar wind and leading to intense auroral activity (Tsurutani & Gonzalez, 1987), with intense substorm activity (Tsurutani et al, 1995, https://doi.org/10.1029/95ja01476). Subsequent work demonstrated that 94% of the HILDCAA periods were associated with high-speed solar wind streams (Hajra et al, 2013), much like the recurrent substorm clusters reported by Rodger et al (2016Rodger et al ( , 2019, and that HILDCAA periods consistently produced enhancements in whistler mode chorus and relativistic electrons measured in geostationary orbit (Hajra et al, 2015).…”
mentioning
confidence: 81%
“…This work initially identified HILDCAA activity present in the magnetosphere linked to large amplitude Alfvén waves in the solar wind and leading to intense auroral activity (Tsurutani & Gonzalez, 1987), with intense substorm activity (Tsurutani et al, 1995, https://doi.org/10.1029/95ja01476). Subsequent work demonstrated that 94% of the HILDCAA periods were associated with high-speed solar wind streams (Hajra et al, 2013), much like the recurrent substorm clusters reported by Rodger et al (2016Rodger et al ( , 2019, and that HILDCAA periods consistently produced enhancements in whistler mode chorus and relativistic electrons measured in geostationary orbit (Hajra et al, 2015).…”
mentioning
confidence: 81%
“…Hence, during indirect magnetopause shadowing the initial particle drift path does not have to directly intersect the magnetopause boundary. Indirect magnetopause shadowing explains electron loss at comparatively low L shells where the magnetopause would never directly impact (e.g., Brautigam & Albert, 2000;Loto'Aniu et al, 2010;Miyoshi et al, 2003;Morley et al, 2010;Rodger et al, 2019;Shprits et al, 2006;Turner et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…To reduce overlap between events, we filtered this list down to a list of 6,276 "clustered" (or "recurrent") substorms (cf. Cresswell-Moorcock et al, 2013 andRodger et al, 2019). The results of this analysis are plotted in Figure S1 in the Supporting Information.…”
Section: Sea Resultsmentioning
confidence: 99%